Etanercept reduces thermal and mechanical orofacial hyperalgesia following inflammation and neuropathic injury. (7th January 2014) - Coelho, S.C.; Bastos‐Pereira, A.L.; Fraga, D.; Chichorro, J.G.; Zampronio, A.R.
Abstract Background This study evaluated the involvement of tumour necrosis factor α (TNF‐α) in orofacial thermal and mechanical hyperalgesia induced by an inflammatory stimulus or by chronic constriction of the infraorbital nerve (CION) using etanercept (Eta), a TNF‐receptor fusion protein that inhibits TNF‐α action. Methods Animals were treated with Eta (0.5 and 5.0 mg/kg, s.c.) or dexamethasone (Dex, 0.5, 1.0 and 2.0 mg/kg, s.c.) and orofacial thermal (cold and heat) and mechanical hyperalgesia induced by an inflammatory stimulus (carrageenan, Cg 50 and 100 μg/lip) or by chronic CION, a model of neuropathic pain in the orofacial region was evaluated. Treatments with Dex or Eta were carried out before Cg or before or after CION. Results Eta or Dex abolished inflammatory thermal and mechanical hyperalgesia. Also, each drug, when given at the day of the surgery and the subsequent day, was effective to abolish thermal and mechanical hyperalgesia induced by CION, assessed on day 4 and on day 13 after the surgery, respectively. However, Eta, but not Dex, given after the CION, abolished thermal and mechanical hyperalgesia and reduced TNF‐α level in the trigeminal ganglion. Conclusions These results suggest that TNF‐α has an important role in cold, heat and mechanical hyperalgesia induced by inflammation or neuropathy in the orofacial region and this may contribute for the establishment of new therapeutic strategies to treat orofacial pain.